2005
DOI: 10.1158/0008-5472.can-04-2221
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Genes Involved in Enhanced Fenretinide-Induced Apoptosis by Parthenolide in Human Hepatoma Cells

Abstract: Fenretinide (N-4-hydroxyphenyl retinamide, 4HPR) is a synthetic anticancer retinoid that is a well-known apoptosisinducing agent. Recently, we observed that the apoptosis induced by fenretinide could be effectively enhanced in hepatoma cells by a concomitant treatment with parthenolide, which is a known inhibitor of nuclear factor-n nB (NF-n nB). Furthermore, treatment with fenretinide triggered the activation of NF-n nB during apoptosis, which could be substantially inhibited by parthenolide, suggesting that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 44 publications
3
38
0
Order By: Relevance
“…In addition, ectopic expression of ANKRD1 in rat embryonic heart cells decreased susceptibility to apoptosis (33), a situation which would be consistent with decreased susceptibility to cisplatin observed with increasing ANKRD1 expression in this study. In contrast, however, ANKRD1 was up-regulated in hepatoma cells in response to fenretinide, an anticancer retinoid, and in this context ANKRD1 has been suggested to be proapoptotic (28). In our cell line model, the sensitive mutant cell line that had lost expression of Ankrd1 had at least three defects related to cisplatin sensitivity: increased drug influx, decreased glutathione levels, and defective DNA repair (34).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…In addition, ectopic expression of ANKRD1 in rat embryonic heart cells decreased susceptibility to apoptosis (33), a situation which would be consistent with decreased susceptibility to cisplatin observed with increasing ANKRD1 expression in this study. In contrast, however, ANKRD1 was up-regulated in hepatoma cells in response to fenretinide, an anticancer retinoid, and in this context ANKRD1 has been suggested to be proapoptotic (28). In our cell line model, the sensitive mutant cell line that had lost expression of Ankrd1 had at least three defects related to cisplatin sensitivity: increased drug influx, decreased glutathione levels, and defective DNA repair (34).…”
Section: Discussionmentioning
confidence: 69%
“…We found ANKRD1 to be expressed in 5 of 9 ovarian cancer cell lines, in 1 of 5 human breast cancer cell lines, and in the majority of serous ovarian adenocarcinomas tested. ANKRD1 has been reported to be expressed in rhabdomyosarcomas (27) and in hepatoma cell lines (28), but to our knowledge this is first report of ANKRD1 expression in human ovarian and breast cancer cells. Moreover, there are few published studies of ANKRD1 expression in response to chemotherapeutic agents, and the data that are available are contradictory.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Recent studies have identified PTL as a potential agent for the treatment of myeloid leukemias, 19 hepatomas 16,17 and cholangiocarcinoma. 18 The data here show that PTL shows a level of cytotoxicity towards CLL cells comparable to or greater than that observed in these earlier studies.…”
Section: Discussionmentioning
confidence: 99%
“…14 The sesquiterpene lactone parthenolide (PTL) has been widely used in traditional medicine for the treatment of migraines and inflammation. 15 This compound has recently been shown to induce apoptosis of hepatoma 16,17 and cholangiocarcinoma 18 cell lines and of primary acute and chronic myeloid leukemia cells 19 in vitro, with IC 50 values varying between 5 and 20 mM. The killing of hepatoma 16 and myeloid leukemia 19 cells was dependent on the PTL-induced generation of reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%